Efektivitas Pembelajaran Digital Berbasis Artificial Intelligence (AI) dalam Mengembangkan Kemampuan Berpikir Kritis dan Literasi Digital Siswa - Herwandi Sape; Lukman Lukman; Muh Ilham (Cerdas: Jurnal Ilmu Pendidikan Sosial dan Humaniora, 2025)
This study aims to examine the effectiveness of artificial intelligence (AI)–based digital learning in developing the critical thinking skills and digital literacy of eighth grade students at SMAN 3 Maros. The research employed a quantitative approach using a quasi experimental nonequivalent control group pretest posttest design. The research sample consisted of 50 students, with 25 students from Class VIII C assigned to the experimental group and 25 students from Class VIII B assigned to the control group. The research instruments included a critical thinking skills test and a digital literacy assessment. Data were analyzed using descriptive statistical techniques. The results indicate that the experimental group experienced a greater improvement in critical thinking skills and digital literacy compared to the control group. The mean critical thinking score of the experimental group increased from 39.76 to 85.08, while the control group increased from 40.36 to 80.36. Similarly, the digital literacy score of the experimental group increased from 36.96 to 82.88, whereas the control group increased from 37.04 to 79.32. These findings confirm that AI based digital learning is effective in enhancing students’ reasoning quality and digital literacy in a more consistent and meaningful manner